KECERDASAN SPIRITUAL DAN SKEPTISME PROFESIONAL SEBAGAI PEMODERASI PENGARUH TIME BUDGET PRESSURE PADA KINERJA AUDITOR - Sari, Tania Purnama; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi, 2017)
Performance auditors questioned, since the occurrence several cases of freezing of public accounting firms as a result of violating the professional standards of public accountants (SPAP). Some research indicates time budget pressure effect on performance, but not always linear. This study aimed to determine the effect of time budget pressure on performance of auditors with spiritual intelligence and professional skepticism as a moderating. Public accounting firm Bali province is the selected location in this study. Data collection method used a questionnaire with non-probability technique sampling and obtained 39 samples. Moderated regression analysis the tool analysis of this study. The results are time budget pressure have negative effect on the performance of auditors, spiritual intelligence is able to strengthen the relationship time budget pressure on the performance of auditors and professional skepticism is able to weaken the relationship time budget pressure on the performance of auditors in the public accounting firm.
Keywords: time budget pressure, spiritual intelligence, professional skepticism, and performance of auditors